Answer:
x intercept is x=3
y intercept is y=-3
Step-by-step explanation:
We can write this equation in a simpler way to find the values needed. Lets do it. Take:
x-y=3
And sum y in both sides, as we know the equality will maintain:
x-y+y=3+y
x = 3+ y
Now subtract 3 in both sides:
x-3 = y+3-3
x-3=y
So, we can rewrite our equation as y=x-3
The x intercept is a value of x such that the equation in equal to zero; in other words, is the value of x when y is zero. It is also called a zero root. Graphically, its the x value when the function passes trough the x-axis. Lets find if, we nned that:
x-3 = 0
If we sum 3 in both sides:
x-3+3=3
x=3
So, x=3 is x intercept
For finding the y intercept we need the value of y when x is zero. Graphically, is the value of y obtained when the function passes trough the y-axis. So, replace x with 0:
0-3=y
y=-3
Another way to get it is knowing that the y intercept in a polynomial is always the independent term, the one that has no x or y, which in this case is -3.
The answer is C: Lincoln uses 25 cents worth of supplies per cup.
All you have to do is substitute the 1 into the m for the mile ride:
C = 0.20(1) + 2.00 = 0.20 + 2.00 = 2.20
The charge for 1 mile ride is $2.20.
<span>2500+150x=3000+125x
150x-125x=3000-2500
25x=500
</span><span>x=500/25
x=20 mo
----------------
2500+150*20=3000+125*20
5500=5500 total paid after each month.</span><span>
</span>